AN ALTERNATIVE HEPATOPROTECTIVE AND ANTIOXIDANT AGENT: THE GERANIUM - Bautista-Avila, Mirandeli; Madrigal-Santillán, Eduardo; Morales-González, Angel; Gayosso-de-Lucio, Juan A.; Madrigal-Bujaidar, Eduardo; Chamorro-Cevallo, German; Alvarez-González, Isela; Benedi, Juana; Aguilar-Faisal, José Leopoldo; Morales-González, Jose A. (African Journal of Traditional, Complementary and Alternative Medicines, 2015)
The Geranium genus is taxonomically classified within the family Geraniaceae Juss, which includes 5-11 genera and nearly 750 species in total. The best-known genera of this family are Geranium, consisting largely of wild plants, and Pelargonium, consisting largely of ornamental plants. Traditional uses include as an antiseptic in wounds and as an antipyretic by infusion of the plant. Currently, eight different species of geraniums belonging to the family Geraniaceae have been identified in Hidalgo State in Central Mexico, and no chemical or pharmacological studies have been carried out in any of these eight species. All phytochemical studies on these species indicate the presence of polyphenolic compounds, including tannins, which are characterized as water-soluble compounds with molecular weights between 500 and 30,000 g/mol. These and other compounds warrant the exploration of the Germanium genus for uses related to ethanol-induced hepatotoxicity.